Capital mobility and asset pricing - Darrell Duffie; Bruno Strulovici (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 2009)
We present a model for the equilibrium movement of capital between asset markets that are distinguished only by the levels of capital invested in each. Investment in that market with the greatest amount of capital earns the lowest risk premium. Intermediaries optimally trade off the costs of intermediation against fees that depend on the gain they can offer to investors for moving their capital to the market with the higher mean return. Those fees also depend on the bargaining power of the investor, in light of potential alternative intermediaries. In equilibrium, the speeds of adjustment of mean returns and of capital between the two markets are increasing in the degree to which capital is imbalanced between the two markets.
Keywords: 330; Kapitalmobilität; Kapitalanlage; Risikoprämie; Kapitalertrag; Theorie